Calculating norms in the spaces l∞(Γ)/c0(Γ) and l∞(Γ)/c(Γ) - Roman Sznajder (International Journal of Mathematics and Mathematical Sciences)
We explicitly compute norms in the quotient spaces l∞(Γ)/c0(Γ) and l∞(Γ)/c(Γ).